Analysis of Muslim Consumer Behavior in Facing Consumption Challenges in the Digital Age - Maulia, Putri Rizqi; Rahmawati, Rahmawati; Mufida, Naily; Wigati, Sri (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This research analyses the impact of digital transformation on Muslim consumption behaviour, particularly impulsive consumption and instant lifestyle. Using qualitative methods and literature review, the research highlights the influence of e-commerce and social media as well as the challenges of hedonism and consumerism. Digitalisation facilitates access to halal products, but also encourages materialism. Islamic value-based digital literacy is needed as a strategy to face this challenge. Islamic consumption awareness needs to be built from an early age through education, da'wah, and consumer protection in order to create a halal, thayyib, and sustainable consumption ecosystem.